2000
DOI: 10.1002/(sici)1097-4636(200005)50:2<191::aid-jbm14>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of segmental bone defects in rabbit radius by biodegradable capsules containing recombinant human bone morphogenetic protein-2

Abstract: Recombinant human bone morphogenetic protein-2 (rhBMP-2) was encapsulated in biodegradable poly(DL-lactide-co-glycolide) (PLGA) capsules to regenerate bone by controlling the release rate of rhBMP-2. The rhBMP-2/PLGA capsules containing 12 microg of rhBMP-2 were implanted in seven 15-mm segmental defects of rabbits radii to examine the healing capacity of the rhBMP-2/PLGA capsules. For the control group, four segmental defects were left empty and two were implanted with ghost PLGA capsules. Healing of the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Although mimicking the geometric architecture of bone in a synthetic scaffold has been shown to promote favorable cellular activity, the overall capacity for a scaffold to direct cell behavior can be substantially improved through the controlled delivery of biospecific cues. 49,[217][218][219][220][221] Administration of growth factors and other bioactive molecules to promote bone formation and repair has achieved promising results in several preclinical and clinical models. [222][223][224][225][226][227] A variety of administration methods have been investigated including: bolus injection, surface adsorbed protein release, osmotic pumps, and controlled release from biodegradable scaffolds.…”
Section: Localized Bioactive Molecule and Drug Delivery In Bone Repairmentioning
confidence: 99%
“…Although mimicking the geometric architecture of bone in a synthetic scaffold has been shown to promote favorable cellular activity, the overall capacity for a scaffold to direct cell behavior can be substantially improved through the controlled delivery of biospecific cues. 49,[217][218][219][220][221] Administration of growth factors and other bioactive molecules to promote bone formation and repair has achieved promising results in several preclinical and clinical models. [222][223][224][225][226][227] A variety of administration methods have been investigated including: bolus injection, surface adsorbed protein release, osmotic pumps, and controlled release from biodegradable scaffolds.…”
Section: Localized Bioactive Molecule and Drug Delivery In Bone Repairmentioning
confidence: 99%
“…5 Polylactideco-glycolide (PLGA) has been approved by the US Food and Drug Administration for certain human clinical applications and has been extensively studied for drug delivery. [6][7][8] As a copolymer of polylactic acid and polyglycolic acid, PLGA is a biodegradable polyester, the variable molecular weight and composition of which can be rationally designed to control the release kinetics of encapsulated therapeutic agents. The incorporation of osteoconductive nano-hydroxyapatite into PLGA can improve the mechanical properties and moderate the degradation rate of the scaffold.…”
Section: Nanomaterials For Bone Regenerationmentioning
confidence: 99%
“…10 Previous studies have shown the ability of BMPs to induce bone formation in a variety of models with many clinical applications in orthopedics and in oral and maxillofacial/dental areas. 11,12 Demineralized freezedried bone allografts (DFDBA), which are known to contain BMPs, have been used and tested extensively for periodontal regeneration. 13 Histologic evidence of enhanced formation of bone, cementum, and connective tissue attachment has been demonstrated in human periodontal defects.…”
Section: Introductionmentioning
confidence: 99%